2020
DOI: 10.3390/brainsci10110862
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidences for an Implication of the Neurodegeneration-Associated Protein TAU in Cancer

Abstract: Neurodegenerative disorders and cancer may appear unrelated illnesses. Yet, epidemiologic studies indicate an inverse correlation between their respective incidences for specific cancers. Possibly explaining these findings, increasing evidence indicates that common molecular pathways are involved, often in opposite manner, in the pathogenesis of both disease families. Genetic mutations in the MAPT gene encoding for TAU protein cause an inherited form of frontotemporal dementia, a neurodegenerative disorder, bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 236 publications
1
30
0
Order By: Relevance
“…The protein Tau is a molecule at the crossroads between brain tumors and neurodegenerative diseases [ 17 , 38 ]. Tau accumulation and aberrant phosphorylation is a driver of Alzheimer’s disease, and Tau expression has also been recognized as a prognosis or predictive marker for chemotherapeutic response in several cancers [ 11 , 17 , 39 ]. In the present work, by down-regulating Tau expression in glioblastoma U87-MG cells, we show that Tau contributes to tumor progression in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein Tau is a molecule at the crossroads between brain tumors and neurodegenerative diseases [ 17 , 38 ]. Tau accumulation and aberrant phosphorylation is a driver of Alzheimer’s disease, and Tau expression has also been recognized as a prognosis or predictive marker for chemotherapeutic response in several cancers [ 11 , 17 , 39 ]. In the present work, by down-regulating Tau expression in glioblastoma U87-MG cells, we show that Tau contributes to tumor progression in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, by down-regulating Tau expression in glioblastoma U87-MG cells, we show that Tau contributes to tumor progression in vivo and in vitro. Available published results suggest that the function of Tau in cancer is dependent on tumor/cell type [ 17 ]. Previous work has shown that MAPT gene expression is enriched in LGGs as compared to GBMs [ 19 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows tau to perform several tasks. Because it will enable cell‐cycle progression while also creating a milieu for cancer cell proliferation aided by tau protein, the microtubule structure is critical during mitotic division 36 …”
Section: Tau Proteinmentioning
confidence: 99%
“…A transcriptomic meta-analysis of three ND types and three cancer types (lung, prostate, and colorectal) demonstrated the inverse comorbidities, and signi cant overlapping genes were found to be upregulated in NDs but downregulated in cancers. They were also found to be downregulated in NDs but upregulated in cancers [2][3][4][5] . One of these molecules, p53, is potentially responsible for regulating the development of NDs and cancer [6][7][8] .…”
Section: Introductionmentioning
confidence: 95%